Trends in Tracheostomy After Stroke: Analysis of the 1994 to 2013 National Inpatient Sample. (October 2018) - Chatterjee, Abhinaba; Chen, Monica; Gialdini, Gino; Reznik, Michael E.; Murthy, Santosh; Kamel, Hooman; Merkler, Alexander E.
Background: Real-world data on long-term trends in the use of tracheostomy after stroke are limited. Methods: Patients who underwent tracheostomy for acute ischemic stroke (AIS), intracerebral hemorrhage (ICH), or subarachnoid hemorrhage (SAH) were identified from the 1994 through 2013 releases of the National Inpatient Sample using previously validated International Classification of Diseases, Ninth Revision, Clinical Modification codes. Survey weights were used to report nationally representative estimates. Our primary outcome was the trend in tracheostomy use during the index stroke hospitalization over the last 20 years. Additionally, we evaluated trends in in-hospital mortality, timing of placement, and discharge disposition among patients who received a tracheostomy. Results: We identified 9.9 million patients with AIS, ICH, or SAH in the United States from 1994 to 2013, of which 170 255 (1.7%; 95% confidence interval [CI]: 1.6%-1.8%) underwent tracheostomy. Among all patients with stroke, tracheostomy use increased from 1.2% (95% CI: 1.1%-1.4%) in 1994 to 1.9% (95% CI: 1.8%-2.1%) in 2013, with similar trends across stroke types. From 1994 to 2013, the timing of tracheostomy decreased from 16.5 days (95% CI: 14.9-18.1 days) to 10.3 days (95% CI: 9.9-10.8 days) after mechanical ventilation. In-hospital mortality decreased from 32.6% (95% CI: 29.1%-36.1%) to 13.8% (95% CI: 12.3%-15.3%) among tracheostomy patients; however, discharge to a nonacute care facility increased from 42.9% (95% CI: 38.0%-47.8%) to 83.3% (95% CI: 81.6%-85.0%) and home discharge declined from 9.3% (95% CI: 7.3%-11.3%) to 2.9% (95% CI: 2.1%-3.7%). Conclusion: Over the past 2 decades, tracheostomy use has increased among patients with stroke. This increase was associated with earlier placement, reduced in-hospital mortality, and lower rates of home discharge.